Environmental policies and media reporting in Sri Lanka / Irvin Weerackody - Weerackody, Irvin (Faculty of Communication and Media Studies (FCMS), 1993)
Several recent developments relating to the field of environmental thought have had a considerable impact upon Sri Lanka's attitude towards ecological issues.